Leadership Communication Strategy of The Fire Rain Organization ot The Jember Tempoe Doeloe Event - Putra, Krisna Laksamana (Journal Of Humanities Community Empowerment, 2025)
In an organization, of course there is good leadership by using appropriate and structured strategies, as Rain Api did in creating the Jember Tempoe Doeloe event. By having a strategy we can achieve our goals more effectively. This research aims to find out the Leadership Communication Strategy of the Rain of Fire Organization at the Jember Tempoe Doeloe Event and to find out the obstacles to the Leadership Communication Strategy of the Rain of Fire Organization at the Jember Tempoe Doeloe Event. This research uses descriptive qualitative methods, it is hoped that it will provide detailed and in-depth information about effective strategies in the Jember Tempoe Doeloe event process using appropriate organizational communication and leadership. The research results show that communication and coordination within the organization play an important role in the strategy process, because this will influence the smoothness of the event and the risk of the event. The leadership used is democratic leadership which requires all Rain Fire members to take part in making decisions, ideas and input. The strategy is structured in several stages such as planning, implementation, evaluation and reporting. So this research can be concluded that the strategy that has been used by the Rain of Fire Organization is very good and very helpful even though there are still several obstacles that occur. The communication strategy for the leadership of the Rain Api organization applies several strategies, including planning, implementation, evaluation and reporting